THE USE OF FORMULAIC EXPRESSIONS IN EFL STUDENTSâ INTERACTIONS - Neno, Hesni; I.R Agustien, Helena (English Education Journal, 2016)
Formulaic expressions are very important for EFL students to be sound natural and fluent in speaking. The study aims at describing types of formulaic expression used by the students, the most frequent types used and why they are used, the studentsâ problems when using formulaic expressions and their strategies to cope with communicative demands. This study was a conversation analysis which used descriptive qualitative approach. The research subjects were nine students from English Study Program in Timor State University in Kefamenanu, East Nusa Tenggara Province. The data were obtained by recording their interactions for one hour each group. The recordings were transcribed and observed as well as two speaking materials used by the teacher when teaching Speaking 1 and Speaking 2. After all data were collected they were classified and analyzed based on Biberâs et al (1999) corpus linguistics. This study showed that the students used collocations, lexical bundles, inserts, idioms, and binomial expressions. The most frequent types were collocations and lexical bundles since the students were more familiar with literal meanings instead of idiomatic meanings. However, there were many unnatural expressions in their interactions therefore formulaic expressions have to get more attention in teaching instruction.